The English Teachers’ Perception toward the Implementation of Educational Unit Level Curriculum (KTSP) and 2013 Curriculum at Junior High School in Tana Toraja Regency - Dan Mangoki (UKI TORAJA, 2015)
The English Teachers’ Perception toward the Implementation of Educational Unit Level Curriculum (KTSP) and 2013 curriculum at Junior High Schools in Tana Toraja Regency. The objective of the research is to find out the English teachers’ perseption toward the implementation of Educational Unit Level Curriculum and 2013 curriculum at junior high schools in Tana Toraja Regency that at the end can be useful information for educational participant.In this research, researcher used the qualitative descriptive method, to describe the English teachers’ perception toward the implementation of Educational Unit Level Curriculum and 2013 curriculum at Junior High Schools in Tana Toraja Regency.The researcher used the procedure of collecting data as follow: the researcer record the interview result and taking note from the interview , obsevation, documentation. The result of this research, generally every teachers has their own understanding toward both curriculum based on their knowladge do they have same even different perception toward both of these curriculum. In concluded, most teacher has good perception toward 2013 curriculum concept and teaching process but prefer KTSPs’ assessment technical the better.